Determinan intensi retur pembelian e-commerce di Indonesia: Model konseptual - Nidya Nurul Aisya; Dekar Urumsah (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2020)
E-commerce is an electronic buying and selling transaction using the internet media. During the Covid-19 pandemic, e-commerce is a solution to shopping efficiently, safely and comfortably, because it can be done from home. However, in e-commerce transactions that do not bring together sellers and buyers directly, it allows for differences in perceptions of the quality of the products and services offered, which will lead to consumer dissatisfaction. This dissatisfaction then results in the emergence of consumers' intention to return products (purchase returns). There are several factors that influence e-commerce purchase return intentions, including: product quality, consumer ethics, and product return policy. This conceptual model is expected to provide insight into both e-commerce providers, e-commerce partners (retailers), and e-commerce consumers so that in practice each party can act without harming each other.Keywords: e-commerce, intention, product return, product quality, consumer ethics, product return policy, TPB.